Hubungan Kemampuan Refleksi Diri dengan Tingkat Stres Mahasiswa Tahun Pertama Program Studi Kedokteran dan Profesi Dokter Fakultas Kedokteran Universitas Tanjungpura, Pontianak, Indonesia: Hasil Penelitian - Faradilla Salsabila; Ita Armyanti; Iit Fitrianingrum (Cermin Dunia Kedokteran, 2024)
Background. Stress is common in daily life, including among medical students. Stress can disrupt their studies and interfere with their individual performance, so it is necessary to manage stress, i.e. through self reflection. Objective: To determine the relationship between self-reflection abilities and stress levels among first-year students of the Medical Study and Medical Profession Education Program, Faculty of Medicine, Tanjungpura University. Methods: An observational analytical cross-sectional study on 141 students selected with a non-probability sampling technique. Data were collected with MAI questionnaires, MSSQ questionnaires, and acute stressor sheets. Analysis was conducted with the Spearman correlation test. Results: There were 107 respondents (75.9%) who had a good ability to self-reflect, and 73 respondents (52.1%) had a moderate level of stress. Spearman correlation test showed a significance value of 0.001 and a correlation coefficient of -0.282. Conclusion: The ability of self-reflection is negatively correlated with stress levels among first-year of Medical Students and Clinical Clerkships at Faculty of Medicine, Tanjungpura University, Pontianak, Indonesia, that the better the ability of self-reflection, the lower the individual’s stress level and vice versa.